Patient Participation in Monitoring Potential Adverse Drug Events - Jorsäter Blomgren, Kerstin; Fastbom, Johan (Applied Clinical Informatics, 2025)
Clinical decision support systems (CDSS) have been suggested to be helpful in detecting and preventing drug-related problems such as adverse drug events (ADEs). However, patient participation systems monitoring self-reported data, such as symptoms, are still sparsely described in the literature.This study aimed to investigate if the use of a patient participating CDSS (PCDSS) can facilitate early detection of ADEs, thereby contributing to safer drug treatment in older adults.A 1-year prospective observational study of elderly patients using a free web-based PCDSS to register symptoms over time at home. Initially, the PCDSS analyzed the extent and quality of the patient's drug use, based on a Swedish national set of criteria, and assessed drug-related symptoms using a standardized scale (PHASE-20). Thereafter, the patients recorded symptoms at home for 1 year—the first 6 months in free text, the second 6 months selecting from 19 predefined symptoms. The PCDSS signaled when symptoms were registered on three occasions in a 3-week period. The patient was then asked to contact his/her nurse at the healthcare center (HCC) for assessment of the symptoms and decisions on further contacts with the nurse or doctor. We analyzed the extent of signals generated, accompanying contacts, and associated medication reviews and adjustments.The 48 study participants registered 1,275 symptoms during the monitoring period, 61% by women. The PCDSS generated a total of 171 signals, of which 58% from women. Seventy-one percent (121) occurred under the first registration (free text) period. Of all signals, 44% (75) led to activities at the HCC, of which 48% (36) were physician contacts. In total, they contributed to medication reviews in 42% (15) and medication adjustments in 64% (23), with a total of 33 adjustments.Patient participation by self-reporting symptoms via a PCDSS can contribute to safer drug use.
Keywords: clinical decision support; adverse drug event; self-reporting; medication review